(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study has shed light on the art of playing musical instruments as a type of fine arts, and has demonstrated that art is based on two pillars in general that include scientific thinking with its required mental and logical capabilities, and aesthetic taste with its delicate emotions. This is true for music as well which is considered an art that is based on science and emotions with all its implementations such as composition and playing. The study also discussed the difference between talent and creativity and their importance in acquiring and developing artistic expertise, as well as understanding the role of creative productivity functions such as fluency, flexibility, and originality in achieving creativity. The study concluded with advice and guidelines for both teachers and students to achieve creativity by staying away from repetition and ill-advised teaching.